2011
DOI: 10.1136/bcr.05.2011.4213
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tunneled Pleural Catheters for the management of Refractory Hepatic Hydrothorax

Abstract: BACKGROUNDHepatic hydrothorax is a complication commonly seen in up to 10% of patients with advanced liver disease. 1 The management of hepatic hydrothorax poses great diffi culties to physicians with current treatment options limited.We present a case where an intrapleural catheter (IPC) was successfully used in the management of a hepatic hydrothorax, improving quality of life and allowing medical management to take effect. There are very few reports of the use of IPC for this indication and we feel others w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…14,15 Some centers have begun using IPCs for treatment of HH. 16,17 Recently, a pilot study with 24 transplant-eligible patients showed the feasibility of this approach. 18 The purpose of the present study was to assess outcomes and complication rates of patients who underwent IPC placement for HH at a large tertiary referral center for patients with advanced liver disease.…”
mentioning
confidence: 99%
“…14,15 Some centers have begun using IPCs for treatment of HH. 16,17 Recently, a pilot study with 24 transplant-eligible patients showed the feasibility of this approach. 18 The purpose of the present study was to assess outcomes and complication rates of patients who underwent IPC placement for HH at a large tertiary referral center for patients with advanced liver disease.…”
mentioning
confidence: 99%
“…The rate of spontaneous pleurodesis after ITPC placement seems to be similar in malignant and non-malignant pleural effusions (about 30%–50%),19–21 24 although the average time to pleurodesis is longer for the last group of patients (about two to four times longer) 18 25. The rate of pleural infection in patients with ITPCs placed for hepatic hydrothorax seems to be higher (8%–16%) than for ITPCs placed for malignant pleural effusion, where rates of 3% have been reported 11 20 22 26.…”
Section: Discussionmentioning
confidence: 91%
“…These catheters allow patients to control pleural fluid output and global hydro and electrolyte states outside the hospital. Curiously, few studies have explored the safety and efficacy of ITPCs for refractory benign pleural effusions, and more specifically, transudative hepatic hydrothorax in patients with advanced cirrhotic liver disease 7 19–23…”
Section: Introductionmentioning
confidence: 99%
“…[ 138 ] Indwelling pleural catheters (IPC) are tunnelled catheters inserted subcutaneously that are often used in the treatment of malignant pleural effusions; although this option is not mentioned by guidelines, some reports showed a favourable cost-effective ratio. [ 139 , 140 ]…”
Section: Hepatic Hydrothoraxmentioning
confidence: 99%